INTERACTION BETWEEN RELIGIOUS PEOPLE POST SOCIAL CONFLICT IN ACEH SINGKIL DISTRICT - Juhari Juhari; Zulfadli Zulfadli (Islam Futura, 2019)
The case Singkil district in October 2015 in the form of inter-religious clashes that led to the burning of churches and loss of life is the fact that social interaction anatar religious adherents in the district of Gunung Meriah has not gone well. This study focused on the background of conflict, the interaction between religious communities after conflict and efforts to foster religious harmony after a conflict in Aceh Singkil. This study used a qualitative approach by using in-depth interviews, Focus Group Discussion (FGD), and study the documentation as data collection techniques. The results showed that the social conflict between religious communities is part of the social dynamics that occur in the community that stretches the inter-religious relations, but on the other hand can strengthen internal solidarity respective faiths. Forms of social interaction leads to the associative process and found to be also the potential that may lead to forms of dissociative interaction. Other forms of social interaction among religions is mutual cooperation, kinship, mutual silaturrahmi and respect among religions. The search results show that during the Aceh Singkil district government has sought to provide guidance to inter-religious harmony though not maximized. This is evident from the Government's efforts impressed yet to find effective strategies for conflict resolution that is holistic, systemic and regenerative. Then it can be predicted that the events of religious conflicts are still likely to occur in the future, both in the district of Gunung Meriah and elsewhere, especially in the district of Aceh Singkil.